Caribbean Report 23-01-1990 - Fraser, Sonia (anchor); Vougy, Fritz (interviewee); Roy, Jean Sebastian (interviewee); Jarman, Brian (correspondent); Buxton, Neil (analyst); Goffe, Leslie (correspondent); Beckwith, David (interviewee); Briley, Harold (correspondent); Smith, Roy (interviewee) (The British Broadcasting Corporation, 1990)
The program features the resignation of the Haitian ambassador in Washington over the exiled opposition leaders from Haiti. According to the Charge d’Affaires at the embassy, the ambassador’s resignation was an emotional blunder. The report also covers the views of the supporters of democracy in Port-au-France who claim that the future of Haiti is in a quandary due to the recent state of siege. Following the Financial Market news, the segment examines the upcoming visit of Dan Quayle, US Vice President to Jamaica to meet with Prime Minister Michael Manley on the US invasion of Panama. The final segment addresses a campaign launched by the British government to facilitate the entry of more black recruits into the British armed forces. According to a report by the Ministry of Defence in Britain, the racial discrimination factor was a major deterrent for applicants of ethnic minorities.
1. Headlines (00:00-00:30)
2. Resignation of the Haitian ambassador in Washington. Interview with Fritz Vougy, Charge d'Affaires at the Haitian Embassy in Washington (00:31-04:46)
3. Supporters of democracy in Haiti concerned about the future of the nation. Brian Jarman interviews Jean Sebastian Roy, son of exiled, Dr. Louis Roy (04:47-08:27)
4. Financial News. Comments from Neil Buxton, metal analyst of Shearson Lehman Hutton Inc. (08:28-09:44)
Keywords: Ambassadors -- Haiti.; Politicians -- Haiti -- Explusion.; Panama -- History -- American Invasion, 1989.; Race discrimination -- England.; Armed Forces -- Minorities -- England.; Jamaica -- Foreign relations -- United States.